Breaking down physical barriers: strategies to improve lymphocyte infiltration for effective neoantigen-based therapies - Chen, Ting-Ting; Li, Xiong; Zhang, Yi; Kang, Xiao-Juan; Zhang, Shu-Fang; Zhang, Tong; Sangmao, Deji; Zhu, Ya-Juan; Zhang, De-Kui (Frontiers in Immunology, 2025)
The cancer genomic instability drives the generation of neoantigens, making them ideal targets for immunotherapy. Neoantigen-specific tumor-infiltrating lymphocytes achieve precise tumor cell killing by recognizing neoantigens on the tumor surface, but their efficacy is limited by complex physical barriers within the tumor microenvironment. These barriers not only directly impede TIL migration and infiltration but also synergize with immunosuppressive signals to weaken antitumor immune responses. The tumor extracellular matrix forms a dense fibrous network due to enhanced collagen crosslinking, pathological hyaluronic acid deposition, and increased stiffness, hindering TIL mobility. Aberrant tumor vasculature, characterized by hyperpermeability and elevated interstitial fluid pressure, collaborates with pro-fibrotic factors, such as VEGF, TGF-β secreted by cancer-associated fibroblasts and regulatory T cells to create mechanical compression barriers. This review systematically explores the composition, molecular mechanisms, and therapeutic strategies targeting these physical barriers, providing novel insights for neoantigen-based therapies. Future efforts should integrate biomechanical interventions with immunotherapy, elucidate the interplay between mechanical signaling and immunometabolism, and optimize multi-target combinatorial approaches to enhance the clinical translation potential of neoantigen therapies.